2022
DOI: 10.1155/2022/6891897
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 MAPK Signalling in Testis Development and Male Fertility

Abstract: The testis is an important male reproductive organ, which ensures reproductive function via the secretion of testosterone and the generation of spermatozoa. Testis development begins in the embryonic period, continues after birth, and generally reaches functional maturation at puberty. The stress-activated kinase, p38 mitogen-activated protein kinase (MAPK), regulates multiple cell processes including proliferation, differentiation, apoptosis, and cellular stress responses. p38 MAPK signalling plays a crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 145 publications
0
20
0
Order By: Relevance
“…Previous studies have demonstrated that the MAPK signaling pathway participated in oxidative stress 23 and that H 2 O 2 and t-BHP could trigger apoptosis by phosphorylating ERK, JNK, and p38 in testis. As shown in Figure 7, compared with the AN group, the phosphorylation levels of JNK and p38 were significantly higher in the DN group although there was no significant change in the phosphorylated ERK.…”
Section: Alteration Of Mitogen-activated Protein Kinases (Mapks) and ...mentioning
confidence: 99%
“…Previous studies have demonstrated that the MAPK signaling pathway participated in oxidative stress 23 and that H 2 O 2 and t-BHP could trigger apoptosis by phosphorylating ERK, JNK, and p38 in testis. As shown in Figure 7, compared with the AN group, the phosphorylation levels of JNK and p38 were significantly higher in the DN group although there was no significant change in the phosphorylated ERK.…”
Section: Alteration Of Mitogen-activated Protein Kinases (Mapks) and ...mentioning
confidence: 99%
“…The p38 MAPKs belong to the MAPK family, playing an essential role in cellular responses including cell proliferation, differentiation, apoptosis, inflammation, and cellular stress responses. 40 Thus, it is important to identify and characterize insect p38 MAPKs to provide a theoretical basis for explaining the Bt insecticidal mechanism. In this study, one p38 MAPK gene was identified from the S. exigua transcriptome and genome database (Figure 1).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Gossypol also impaired mouse testicular development through mitogen-activated protein kinase pathway inactivation [ 29 ]. Mitogen-activated protein kinase pathway was crucial signaling during spermatogenesis integrating its role in cell proliferation, differentiation, apoptosis, and cellular stress response [ 39 , 40 ]. Gossypol also interferes with the expression of several genes associated with testicular development, such as cell proliferation, spermatogenesis, and maturation of germ cells [ 29 ].…”
Section: Discussionmentioning
confidence: 99%